Parallel multi-image encryption based on cross-plane DNA manipulation and a novel 2D chaotic system - Zhang, Zhibo; Zhang, Jindong (The Visual computer, 2024)
In this paper, we propose a novel parallel multi-image encryption algorithm based on cross-plane DNA operations. Firstly, a two-dimensional chaotic system, 2D-SCIM, is constructed. Secondly, for a set of images, whether they are color images, grayscale images, or their combinations, we perform bit-plane decomposition according to the channels without limitations on quantity and arrangement order. Subsequently, the low and high bit planes are paired and encoded into DNA planes using chaotic sequences. Next, the DNA planes undergo two rounds of cross-plane diffusion and cross-plane cyclic shifting in parallel threads, where the chaotic sequence controls the encoding, direction, order, and operations of diffusion and cyclic shifting. Finally, the original image structure is used to combine the bit planes and obtain the encrypted image set. Security analyses, including key sensitivity, histograms, correlations, information entropy, differential attacks, noise attacks, and encryption speed, are conducted on the algorithm. Experimental results demonstrate that the proposed image encryption algorithm effectively withstands various attacks.